EDUCATION UNDER CONFLICT: CRISIS MANAGEMENT AT DISPLACED UNIVERSITIES IN UKRAINE - Gladushyna, Olesya (The Modern Higher Education Review, 2020)
The study deals with the retrospective investigation of the predominant factors that influenced the performance of displaced universities from Eastern Ukraine under the armed conflict. The research also sought to examine the goals and strategies pertinent to university management teams at different stages of crisis and in different dimensions. To achieve this, questionnaire was chosen as a research instrument to collect data that was further analysed and grouped into overarching themes. Based on the research results, the study provides recommendations for multiple stakeholder groups on enhancing the crisis management techniques at higher education institutions in Ukraine, in particular at displaced universities. Moreover, the paper suggests further directions in researching the crisis management in Ukrainian higher education in order to improve the preparedness of universities to emergency and crisis situations as well as to boost the effectiveness of management planning, decision-making and implementation processes.